Córdoba, Spanien. Madīnat al-Zahrā’. Die Arbeiten der Jahre 2020 und 2021 - Arnold, Felix (e-Forschungsberichte des DAI, 2021)
Outside of Córdoba (Spain), the remains of the palatial city of a caliph are preserved: Madīnat al-Zahrāʼ. An ongoing cooperation project focuses on the Plaza de Armas, a huge esplanade outside the caliph’s residence. Excavations at the north-east corner of the plaza have provided new insights into its structural development, from its formation as the forecourt of the ruler’s palace to the construction of monumental porticos. Iron elements found at a gate have been restored and analyzed, and the city’s garden area visualized. In addition a new project has been initiated to document and investigate one of the audience halls of the caliph. The investigations provide new insights into the transformation of the caliphate and its representation in architecture.